Sentence length and recidivism: Court rulings based on BAC - Joakim Jansson; Per Pettersson-Lidbom; Mikael Priks; Björn Tyrefors (Research Institute of Industrial Economics (IFN), 2025)
We study the effect of prison sentences on recidivism using a unique feature of sentencing for drunk driving in the Swedish court system. Below the blood alcohol concentration (BAC) of 1.0, individuals are never sentenced to prison and above 1.0, the average number of days sentenced to prison is essentially linearly increasing with the BAC level. We find that being sentenced to prison for one month reduces reoffending in the next five years by approximately 80 percent.
Keywords: K42; R41; C26; 330; Sentence length; Recidivism; DUI